Predictors and prognostic impact of early acute kidney injury in cardiogenic shock: results from a monocentric, prospective registry - Schupp, Tobias; Behnes, Michael; Rusnak, Jonas; Weidner, Kathrin; Ruka, Marinela; Dudda, Jonas; Schmitt, Alexander; Forner, Jan; Egner-Walter, Sascha; Ayasse, Niklas; Bertsch, Thomas; Kittel, Maximilian; et al. (Cardiorenal Medicine, 2024)
Introduction: The presence of acute kidney injury (AKI) was shown to increase the risk of mortality following acute myocardial infarction; however, data regarding the prognostic impact of early AKI in patients with concomitant cardiogenic shock (CS) is limited. The study investigates predictors and the prognostic impact of AKI in patients with CS. Methods: Consecutive patients with CS from 2019 to 2021 were included at one institution. Laboratory values were retrieved from day of disease onset (day 1) and days 2, 3, 4, and 8 thereafter. Predictors for AKI (defined as an increase of plasma creatinine >50% within 48 h referring to pre-admission or baseline creatinine on day 1 and/or the need for continuous veno-venous hemodiafiltration [CVVHDF]) and the prognostic impact of early AKI with regard to 30-day all-cause mortality were assessed. Statistical analyses included t test, Spearman’s correlation, C-statistics, Kaplan-Meier, and Cox proportional regression analyses. Results: A total of 219 CS patients were included with an incidence of early CS-related AKI of 52%. With an area under the curve of up to 0.689 (p = 0.001), creatine discriminated 30-day mortality in CS. Increasing lactate levels (OR = 1.194; 95% CI: 1.083-1.316; p = 0.001; per increase of 1 mmol/L) was associated with the occurrence of AKI. The presence of AKI was associated with an increased risk of 30-day all-cause mortality (63% vs. 36%; HR = 2.138; 95% CI: 1.441-3.171; p = 0.001), even after multivariable adjustment (HR = 1.861; 95% CI: 1.207-2.869; p = 0.005). Finally, highest risk of all-cause mortality was observed in patients with AKI requiring CVVHDF (75% vs. 44%; log rank p = 0.001; HR = 2.211; 95% CI: 1.315-3.718; p = 0.003). Conclusion: Early AKI affects more than half of patients with CS and is independently associated with 30-day all-cause mortality in CS, with highest risk of death among patients with AKI requiring CVVHDF.